Pengaruh Dukungan Sosial Guru Terhadap Motivasi Berprestasi - Petrus Logo Radja; Fredericksen Victoranto Amseke (Institut Agama Kristen Negeri Manado, 2024)
Vocational high school is a secondary education unit that not only prepares students for obtaining achievement in the classroom but also makes students become skilled workers who are ready to enter the working world. In gaining achievements and becoming skilled workers, students need achievement motivation which is influenced by the social support provided by the teacher. This research aimed to determine the influence of teacher social support on student achievement motivation. This research used quantitative methods. The data collection tool applied the teacher social support scale and the achievement motivation scale. The population was 354 grade XI students at SMK Negeri 5 Kupang. The sample of 35 students with the sampling technique used was Cluster Random Sampling. The analysis used simple linear regression analysis. The result showed that teacher social support had a positive and significant contribution to student achievement motivation with an R Square value of 38.8%. Teacher social support has a positive and significant effect on achievement motivation of vocational school students. Teachers are expected to provide social support to each student so that students have achievement motivation to achieve success in learning and the workplace.